A novel nonsense PTH1R variant shows incomplete penetrance of primary failure of eruption: a case report - Cristina Grippaudo; Concetta Cafiero; Isabella D'Apolito; Agnese Re; Maurizio Genuardi; Pietro Chiurazzi; Sylvia A. Frazier-Bowers (BMC, 2019)
Abstract Background Aim of this work was to describe a rare inheritance pattern of Primary Failure of Eruption (PFE) in a small family with incomplete penetrance of PFE and a novel nonsense PTH1R variant. Case presentation The proband, a 26 year-old man with a significant bilateral open-bite, was diagnosed with PFE using clinical and radiographic characteristics. DNA was extracted from the proband and his immediate family using buccal swabs and the entire PTH1R coding sequence was analyzed, revealing a novel heterozygous nonsense variant in exon 7 of PTH1R (c.505G > T). This variant introduces a premature stop codon in position 169, predicted to result in the production of a truncated and non-functional protein. This variant has never been reported in association with PFE and is not present in the Genome Aggregation Database (gnomAD). Interestingly, the c.505G > T variant has also been identified in the unaffected mother of our proband, suggesting incomplete penetrance of PFE. Conclusions In this study, we report a new PTH1R variant that segregates in an autosomal dominant pattern and causes PFE with incomplete penetrance. This underlines the diagnostic value of a thorough clinical and genetic analysis of all family members in order to estimate accurate recurrence risks, identify subtle clinical manifestations and provide proper management of PFE patients.